Reliability of trail walking and running tasks using the Stryd Power Meter - Navalta, J. W.; Montes, J.; Bodell, N. G.; Aguilar, C. D.; Radzak, K.; Manning, J. W.; DeBeliso, M. (International Journal of Sports Medicine, 2019)
Footpod monitors are wearable devices attaching to the shoe with the ability to sense oscillations in leg movement; however, few studies provide reliability. The purpose was to provide reliability data for outdoor tasks as measured by the Stryd Power Meter, which is a footpod monitor. Young healthy individuals (N=20, male n=12, female n=8) completed two 5-min self-paced walks along a trail, and two 5-min trail runs. Reliability of the tasks was determined using Coefficient of Variation (CV), Intraclass Correlation (ICC), and 95% confidence intervals (CI). Measures during trail running that returned a CV less than 10%, met the ICC threshold of 0.70, and displayed good to excellent 95% CI included pace, average elapsed power, average elapsed form power, average elapsed leg spring, and vertical oscillation. The only variable during walking to meet these criteria was maximal power (CV=4.02%, ICC=0.968, CI=0.902, 0.989). Running tasks completed on a trail generally return more consistent measures for variables that can be obtained from the Stryd footpod device than walking tasks.